Survey of Australian equine veterinarians evaluating their biosecurity training and perceptions and opinions about the management of the 2007 equine influenza outbreak. Issue 4 (April 2014) - Schemann, K; Toribio, J‐ALML; Taylor, MR; Ward, MP; Dhand, NK
<x xml:space="preserve">Abstract</x> Objectives To evaluate the level of biosecurity training among Australian equine veterinarians and to assess their perceptions of biosecurity and infectious disease risk and their opinions about the management of the 2007 equine influenza (EI) outbreak. Design Cross‐sectional study. Methods A survey was conducted among equine veterinarians attending the 2010 annual conference of the Equine Veterinarians Australia (EVA) in New South Wales, Australia. Data were collected using a self‐completed questionnaire and analysed using Fisher's exact tests to assess veterinarians' levels of biosecurity training, their perceptions of infectious disease and views regarding the 2007 EI outbreak management. Results A total of 46 of the 196 (23.5%) attending veterinarians completed the questionnaire. Significantly greater proportions of recently graduated veterinarians received theoretical and practical biosecurity training at veterinary schools than their older counterparts. The majority of respondents considered their likelihood of spreading infectious diseases from one client's horse to another to be low (84%). More than half (58%) of the veterinarians considered that hand‐washing/wearing gloves was very effective in preventing disease spread. However, around one‐quarter (27%) reported a degree of reservation about the practicality of performing general biosecurity practices in everyday working life. Overall, veterinarians were satisfied with the EI outbreak response, but had mixed opinions about the control measures and communications used. Conclusion Levels of biosecurity training and the frequency of biosecurity advice provided by veterinarians have increased over time, although the practicality of biosecurity practices is a concern for some veterinarians. Further investigations of the barriers to the use of various biosecurity practices are required in order to inform training programs.